2011
DOI: 10.1182/blood-2011-01-332064
|View full text |Cite
|
Sign up to set email alerts
|

Human lymphoblastoid B-cell lines reprogrammed to EBV-free induced pluripotent stem cells

Abstract: Generation of patient-specific induced pluripotent cells (iPSCs) holds great promise for regenerative medicine. Epstein-Barr virus immortalized lymphoblastoid B-cell lines (LCLs) can be generated from a minimal amount of blood and are banked worldwide as cellular reference material for immunologic or genetic analysis of pedigreed study populations.We report the generation of iPSCs from 2 LCLs (LCL-iPSCs) via a feeder-free episomal method using a cocktail of transcription factors and small molecules. LCL-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 21 publications
3
77
0
Order By: Relevance
“…43 Even though the parental cell lines expressed viral EBNA1 and other Epstein-Barr virus-related elements, these were not detectable in LCL-iPSCs. LCLs harbor artifacts such as point mutations and CNVs, but lines with mutations confirmed in nontransformed cells could provide a source for known high-risk genetic factors such as specific CNVs.…”
Section: Reprogramming and Cell Sourcesmentioning
confidence: 95%
“…43 Even though the parental cell lines expressed viral EBNA1 and other Epstein-Barr virus-related elements, these were not detectable in LCL-iPSCs. LCLs harbor artifacts such as point mutations and CNVs, but lines with mutations confirmed in nontransformed cells could provide a source for known high-risk genetic factors such as specific CNVs.…”
Section: Reprogramming and Cell Sourcesmentioning
confidence: 95%
“…Blood sample collection and storage are among the routine procedures in hospitals and clinics. Therefore, significant efforts have been made to develop efficient and safe procedures for reprogramming various types of blood cells (Table 1) [10,11,[13][14][15][16][17][18][19][20][21]. Umbilical cord blood (UCB) cell banks provide another rich source for cells with diverse HLA types.…”
Section: Generation Of Patient-specific Ipscsmentioning
confidence: 99%
“…These successes allowed efficient generation of patient-specific iPSCs with intact genomes from convenient cell sources. More recently, it has been shown that EBV-immortalized lymphoblast cells (established originally from blood MNCs) can also be reprogrammed to EBV genome-free iPSCs [20,21]. EBV-immortalized lymphoblasts may have additional somatic mutations (see below for discussion on somatic mutations found in iPSCs) and therefore are not preferred choice as a source of iPSCs to be used in cell therapy.…”
Section: Generation Of Patient-specific Ipscsmentioning
confidence: 99%
“…iPSCs for dissecting complex disease mechanisms and studying genetics Current models for dissecting the genetics underlying complex diseases rely on genome wide association studies (GWAS) performed on human samples from populations with or without the disease of interest [3,6]. Typically, these GWAS involve sample collections of blood, from which DNA is extracted for SNP genotyping analysis.…”
Section: Why Ipscs and Africa?mentioning
confidence: 99%